Assessing the benefits of multisensory audiotactile stimulation for overweight individuals. - Wan, X; Spence, C; Mu, B; Zhou, X; Ho, C (2014)
We report an experiment designed to examine whether individuals who are overweight would perform differently when trying to detect and/or discriminate auditory, vibrotactile, and audiotactile targets. The vibrotactile stimuli were delivered either to the participant's abdomen or to his hand. Thirty-six young male participants were classified into normal, underweight, or overweight groups based on their body mass index. All three groups exhibited a significant benefit of multisensory (over the best of the unisensory) stimulation, but the magnitude of this benefit was modulated by the weight of the participant, the task, and the location from which the vibrotactile stimuli happened to be presented. For the detection task, the overweight group exhibited a significantly smaller benefit than the underweight group. In the discrimination task, the overweight group showed significantly more benefits than the other two groups when the vibrotactile stimuli were delivered to their hands, but not when the stimuli were delivered to their abdomens. These results might raise some interesting questions regarding the mechanisms underlying audiotactile information processing and have applied relevance for the design of the most effective warning signal (e.g., for drivers).